Partnerships in Translation: Advancing Research and Clinical Care.: The 14(th) Annual HMO Research Network Conference, April 13–16, 2008, Minneapolis, Minnesota - Greenlee, Robert T. (Marshfield Clinic, 2008)
The Health Maintenance Organization Research Network held its annual meeting in Minneapolis in April of 2008, with more than 300 investigators, research staff, clinical leaders, and academic partners gathering in conjunction with the conference theme ‘Partnerships in Translation: Advancing Research and Clinical Care.’ This article provides some background on the network, its research activities, and the annual conference. Also featured is an article by Coleman and colleagues summarizing the conference’s first plenary session, where operational leaders of health care organizations discussed the optimization of health care through research. This issue of Clinical Medicine & Research also includes a selection of scientific abstracts presented at the meeting on a wide range of clinical and population health topics.